LES MISÉRABLES: The Tale of COVID-19 and Role of Information. Issue 2 (3rd April 2021) - French, Aaron M.; Storey, Veda C.; Wallace, Linda
ABSTRACT: As researchers, scientists, and the general public strive to understand and manage COVID-19, many people search the internet for clues that might help them understand and react to the virus in an informed manner. Social media has become a primary source of news for many, but it can also be a hindrance in managing crisis situations due to the prevalence of fake news. This paper reports on a survey administered to social media users during the first wave of the pandemic to identify perceptions and areas of conflict that influenced society's ability to understand and contain the pandemic. Applying conflict resolution theory to the survey results enabled us to identify major issues related to the management of COVID-19, from which we made recommendations for the roles that information systems research can play in handling future pandemics or other crises. The recommendations are divided into the two general categories of media trust and crisis containment.